Reduction o share capital and protection of creditors - Arsić, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
In case of reduction of share capital creditors whose claim arose prior expiration of 30 days from announcement of the resolution of reduction of share capital have the right to demand security. This right exists irrespective of whether claims are due or not. Rules on protection of creditors shall not apply in some cases where annulment of shares takes place and where difference among property of company and its obligations remains unchanged. The right to demand security shall not be available to creditors who in the case of insolvency proceedings have the right to preferential payment or whose claims are already secured. Creditors are authorized to apply to judicial authority for adequate safeguards.